Nilai Tanggung Jawab dalam Pementasan Wayang Wong dengan Lakon Kikis Tunggorono oleh Sanggar Wiraga Apuletan - Jamal, Caesar; Muslimin, Genta Rafi (Universitas Hamzanwadi, 2024)
Character education is an important component in developing the personality of each individual in a nation. The government's efforts to support the development of education are evidenced by the existence of Presidential Regulation No 87 of 2017 article 2 which states that there are 18 character education values, one of which is responsibility. However, the efforts made by the government have not been successful. The number of cases of misuse of power is clear evidence that the value of responsibility has not been applied properly in each individual. The lack of the value of responsibility for a mandate is the background of the research on the value of responsibility character education in the wayang wong performance with the play